Boundary state of a analogue of the half-infinite t − J model. (25th February 2016) - Kojima, Takeo
Abstract: A -analogue of the half-infinite t   −   J model with a boundary is studied by using the vertex operator approach. We find an explicit bosonic formula of the boundary state in the integrable highest-weight module over the quantum superalgebra .